2010
DOI: 10.1007/s11033-010-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel SNP of the ATP1A1 gene is associated with heat tolerance traits in dairy cows

Abstract: PCR low ionic strength single-strand conformation polymorphism (PCR-LIS-SSCP) and DNA sequencing methods were used to analyze the polymorphisms within the coding region of bovine ATP1A1 gene. A novel C/A mutation was identified at the nucleotide position 2789 of the ATP1A1 mRNA, but it was silent with respect to the amino acid sequence of the protein. The LIS-SSCP banding pattern could be divided into three kinds of genotypes, named CC, CA, and AA. Also, the association of the novel SNP of ATP1A1 gene with hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 31 publications
5
73
1
2
Order By: Relevance
“…A number of researches in genome-wide SNP genotyping has been progressively achieved, such as cost-effective dairy cattle breeding programs (Hayes et al2009), useful information on genetic variation of Korean Hanwoo breed (Dadi et al 2012) and indicine and African cattle breeds (Matukumalli et al 2009), and genome wide association for milk production in Danish Jersey cattle (May et al 2010). Specific SNPs associated with genes have also been elucidated their association with targeted traits in dairy and beef cattle (Liu et al 2011;Lu et al 2011;Deb et al 2014). Thus, our study is relevant with previous studies using Bovine SNP array conducted in many countries to offer a useful knowledge and promise for improving targeted traits in cattle.…”
Section: Gucy2cplbd1supporting
confidence: 54%
“…A number of researches in genome-wide SNP genotyping has been progressively achieved, such as cost-effective dairy cattle breeding programs (Hayes et al2009), useful information on genetic variation of Korean Hanwoo breed (Dadi et al 2012) and indicine and African cattle breeds (Matukumalli et al 2009), and genome wide association for milk production in Danish Jersey cattle (May et al 2010). Specific SNPs associated with genes have also been elucidated their association with targeted traits in dairy and beef cattle (Liu et al 2011;Lu et al 2011;Deb et al 2014). Thus, our study is relevant with previous studies using Bovine SNP array conducted in many countries to offer a useful knowledge and promise for improving targeted traits in cattle.…”
Section: Gucy2cplbd1supporting
confidence: 54%
“…7). Though the activation of HSPs in response to heat stress is very well characterized, polymorphism in these genes could be associated with milk yield in lactating cattle Liu et al 2011); moreover, the expression of these genes could also be verified for their effect on milk yield in lactating cows in the hot season.…”
Section: Heat Stress Resulted In the Activation Of Heat Shock Factorsmentioning
confidence: 99%
“…Chen et al (2013) indicated that SNP C.-141G>A in the 5'-flanking region of the Hsp90b gene in chickens had some effect on thermotolerance traits, and this might be a potential molecular marker of thermotolerance. Liu et al (2011) found that a novel SNP of the ATP1A1 gene is associated with heat tolerance traits in dairy cows. In this study, 10 SNPs were identified in a 2400-bp 5'-flanking region of the chicken GRP78 gene, and seven of these polymorphism sites caused transcription factor binding sites to disappear, occur, or change.…”
Section: Discussionmentioning
confidence: 98%